Topological Properties of Supramolecular Chain of Different Complexes of N-Salicylidene-L-Valine. (21st October 2022) - Afzal Siddiqui, Hafiz Muhammad; Nadeem, Muhammad Faisal; Azeem, Muhammad; Arshad, Muhammad Adeel; Haider, Ali; Malik, Muhammad Aslam
Abstract: L-valine is considered one of the essential amino acids for mammals, which belongs to the glycogen types of amino acids. This amino acid is valuable for making protein. Due to the diverse structure of N-salicylidene-L-valine and its higher catalytic and cytotoxic activity it gains impressive interest. To study this structure more deeply and to know more about its properties in terms of topological indices, we study the supramolecular chain in dialkyltin of complex- 2, 3, and 4 of N-salicylidene-L-valine. In the end, we provide a comparative study of these structures by taking particular examples and also gives a comparison between topological indices.